High temperature limits on developmental canalization in the ascidian Ciona intestinalis. (June 2019) - Irvine, Steven Q.; McNulty, Katherine B.; Siler, Evelyn M.; Jacobson, Rose E.
Abstract: The normal embryogenesis of marine animals is typically confined to a species-specific range of temperatures. Within that temperature range development results in a consistent, or canalized, phenotype, whereas above and below the range abnormal phenotypes are produced. This study reveals a high temperature threshold, occurring over a 1–2 °C range, for normal embryonic development in C. intestinalis . Above that threshold the prevalence of morphological abnormalities increases significantly, beginning with cleavage and gastrula stages, and becoming more pronounced as embryogenesis proceeds. However, even in highly morphologically abnormal temperature disrupted (TD) embryos, muscle, endoderm, notochord, epidermis, and sensory pigment cells are recognizable, as evidenced by histochemical markers or morphology. On the other hand, morphogenesis of the notochord and other structures is dependent on precise cell movement and shape changes after the gastrula stage, which are disrupted above the high temperature threshold. These findings suggest that morphogenetic processes may be more sensitive to high temperature than cell type specification events. They also point to avenues for investigation of the limiting factors to developmental canalization in marine invertebrates. Highlights: C. intestinalis has a high temperature threshold, within 1–2 °C, for normal canalized embryogenesis In abnormal temperature disrupted (TD) embryos, muscle, endoderm, notochord, epidermis, and sensory pigment cells are still recognizable Abnormalities from rearing temperatures over the maximal threshold are characterized by live imaging and confocal microscopy